UseLess club - Ng, Phoebe Zi Ying (Nanyang Technological University, 2023)
This project aims to tackle the issue of paper waste created by National Technological University (NTU) School of Art Design and Media (ADM) Visual Communication (VC) students by implementing a circular system of management within the department. By creatively repurposing the design waste generated by design students, this project hopes to reduce the amount of paper waste that ends up in landfills and encourage more sustainable practices within the design community. The goal is to start small and create a possible model that can be replicated in other departments and institutions that have paper waste, and contribute towards a more sustainable and environmentally conscious society.